(untitled) (Journal of Geography and Environmental Management, 2017)
Organization of tourism and recreation presupposes the existence of certain prerequisites of the territory. These prerequisites may be involved in tourist activities, which is a multidimensional phenomenon. The difficulty lies in the accounting and knowledge of the prerequisites of certain territory. In the article it is come under review the adoption of the assessment of Aggregate Tourism Potential, which is based on the cartographic method of research, on the example of Kazakhstan. During the process of research, we made extensive use of statistical, mathematical, cartographic methods and the method of computer modeling of geographic information systems (GIS), as well as the methodology of the assessment of Aggregate Tourism Potential of territory, whose author is Stanislav R. Erdavletov. The methodology of the assessment of Aggregate Tourism Potential consists of logical fulfilling of several stages. The methodology is based on the method of grade bonitation of territory. In addition to that, we focus a lot on the cartographic method of research, which is aimed at a comprehensive vision of the research problems, while having a visual effect. In consequence of research, it was determined that the Aggregate Tourism Potential of the territory of Kazakhstan is 10003 points. Based on experimental and quantitative data taxonomy and allocation of oblasts and regions of the country were held according to the Aggregate Tourism Potential. The result of the research is the complex map of the development of tourism on the territory of the Republic of Kazakhstan.